High CD49f expression is associated with osteosarcoma tumor progression: a study using patient‐derived primary cell cultures. (7th May 2014) - Penfornis, Patrice; Cai, David Z.; Harris, Michael R.; Walker, Ryan; Licini, David; Fernandes, Joseph D. A.; Orr, Griffin; Koganti, Tejaswi; Hicks, Chindo; Induru, Spandana; Meyer, Mark S.; Khokha, Rama; et al.
Abstract Overall prognosis for osteosarcoma (OS) is poor despite aggressive treatment options. Limited access to primary tumors, technical challenges in processing OS tissues, and the lack of well‐characterized primary cell cultures has hindered our ability to fully understand the properties of OS tumor initiation and progression. In this study, we have isolated and characterized cell cultures derived from four central high‐grade human OS samples. Furthermore, we used the cell cultures to study the role of CD49f in OS progression. Recent studies have implicated CD49f in stemness and multipotency of both cancer stem cells and mesenchymal stem cells. Therefore, we investigated the role of CD49f in osteosarcomagenesis. First, single cell suspensions of tumor biopsies were subcultured and characterized for cell surface marker expression. Next, we characterized the growth and differentiation properties, sensitivity to chemotherapy drugs, and anchorage‐independent growth. Xenograft assays showed that cell populations expressing CD49fhi/CD90lo cell phenotype produced an aggressive tumor. Multiple lines of evidence demonstrated that inhibiting CD49f decreased the tumor‐forming ability. Furthermore, the CD49fhi/CD90lo cell population is generating more aggressive OS tumor growth and indicating this cell surface marker could be a potential candidate for the isolation of an aggressive cell type in OSs.